2000
DOI: 10.1002/1522-7278(2000)15:5<558::aid-tox29>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Algal toxins?Initiators of avian botulism?

Abstract: An outbreak of avian botulism in Whitewater Lake, Manitoba, Canada was associated with reducing sediments. But any linkage between sediments and botulism was only indirect; Clostridium botulinum was not observed in the sediments. The source of the C. botulinum was unclear but carcasses that overwintered appeared to perpetuate the outbreak. The algal toxins anatoxin-a and ( ) microcystin-LR were present 17 ( mg/ L when many birds were moulting and unable to fly, likely making them more sensitive to botulism. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 20 publications
2
23
0
2
Order By: Relevance
“…These factors include temperature, salinity of the substrate, pH, redox potential (of the surface water and soil/sediment pore water), dissolved oxygen level, and sediment/soil organic matter content (24,45,46). Moreover, large epidemic outbreaks are favored by the presence of botulism intoxicated avian carcasses and the maggots that feed on them.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include temperature, salinity of the substrate, pH, redox potential (of the surface water and soil/sediment pore water), dissolved oxygen level, and sediment/soil organic matter content (24,45,46). Moreover, large epidemic outbreaks are favored by the presence of botulism intoxicated avian carcasses and the maggots that feed on them.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lake conditions reported in this study indicate that physico-chemical and biological changes occurred through the sampling season, and we found that the significant correlations in the study were in agreement with other studies' environmental findings in relation to the ecology of C. botulinum (Huss et al, 1979;Rocke & Samuel, 1999;Murphy et al, 2000). The nearsediment conditions we studied have not been reported previously for Lake Erie in connection with a botulism outbreak-year.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also observed links between changes in environmental characteristics of wetlands that can be due to eutrophication and botulism. Murphy et al (40) found that a change in the water Eh in Whitewater Lake (Canada) might have been a significant factor in the development of C. botulinum type C in its sediments. Rocke et al (41) found that increasing temperature and biomass may influence the initial phase of botulism outbreaks and that these were more frequent in wetlands with lower Eh.…”
Section: ϫmentioning
confidence: 99%